(untitled) (Dhaka University Journal of Biological Sciences, 2016)
An experiment was carried out to find the salinity tolerance capability and growth performance of Climbing Perch, Anabas testudineus (Bloch, 1795). Anabas testudineus commonly cultured fish in Bangladesh was reared in laboratory conditions at different salinities of 0, 3, 6, 9, 12, 15, 18 and 21 for 60 days. Hundred per cent survivals were detected at 0, 3, 6 and 9 salinity while 100% mortality was recorded at 18 and 21 salinity. Various responses to threat and feeding were observed among the fish in different treatments. Lowest feed conversion ratio was found in the control group while the highest was detected at 15 salinity. On the other hand, decreasing trend of specific growth and average growth rate were observed in A. testudineus fingerlings from 0 to 15 salinity. Significantly higher specific growth rate and average growth rate were detected in A. testudineus fingerlings reared at 0 - 6 salinity (p < 0.05). The present study suggests that Climbing Perch fingerlings can be reared at fresh water growth rates in coastal water with salinity up to 6. Dhaka Univ. J. Biol. Sci. 25(1): 65-73, 2016